Pengaruh Perencanaan Terhadap Pembangunan Desa Dengan Pengelolaan Keuangan Sebagai Variabel Intervening: Studi di Kecamatan Wonosari Kabupaten Boalemo Provinsi Gorontalo - Nurain Samsudin; Syarwani Canon; Harun Blongkod (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze: (1) the influence of planning on village development, (2) the influence of financial management on village development, (3) the influence of planning on village financial management, and (4) the mediating role of financial management in the relationship between planning and village development in Wonosari District, Boalemo Regency, Gorontalo Province. This research employs a quantitative method using primary data obtained through questionnaires measured with a Likert scale. The sample was selected using purposive sampling technique. Data analysis was conducted using Structural Equation Modelling (SEM) with the assistance of SPSS and AMOS 24 software. The results of the study indicate that: (1) planning has a direct and positive effect on village development; (2) financial management has a direct and positive effect on village development; (3) planning has a direct and positive effect on village financial management; and (4) financial management significantly mediates the effect of planning on village development.